ARZombie: A mobile augmented reality game with multimodal interaction - Cordeiro, Diogo (2019)
Augmented reality games have the power to extend virtual gaming into real world scenarios with real people, while enhancing the senses of the user. This paper describes the ARZombie game developed with the aim of studying and developing mobile augmented reality applications, specifically for tablets, using face recognition interaction techniques. The goal of the ARZombie player is to kill zombies that are detected through the display of the device. Instead of using markers as a mean of tracking the zombies, this game incorporates a facial recognition system, which will enhance the user experience by improving the interaction of players with the real world. As the player moves around the environment, the game will display virtual zombies on the screen if the detected faces are recognized as belonging to the class of the zombies. ARZombie was tested with users to evaluate the interaction proposals and its components were evaluated regarding the performance in order to ensure a better gaming experience.